Colaboration of Make a Match by Giving Questions and Getting Answers Using Domino Cards to Improve Student Activity and Mathematics Learning Outcomes - Ghofirotul Mardiah (Universitas Islam Jember, 2018)
Learning is a key activity of the education proces. Researchers conducted observation in class VII MTs Sirojul Ulum Virgin. This study description aktivity and study results in studying the operational aljabar with tipe Make A Match and Giving Question And Getting Answer make Card Domino. Type of researc is a classroom action research (CAR). The procedure used is the model cycle, mean persentesion activity studyig in the first cycle of 69,14%, while in the second cycle is 80,53%. Then the results of pretest of students of 50,00%, while in the first cycle of 61.11%, while in the second cycle of 94,44%. It means that the activity and student learning outcomes can be improved with the implementation of cooperative learning model type Make A Match And Giving Question And Getting Answer make Card Domino. The learning model is used for improve motivation student in question and have keative answered to prove the problem. Keyword: Make a Match and Giving Question and Getting Answer, domino card, learning activity and learning outcomes.